2021
DOI: 10.3390/biom11121870
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing for Glioblastoma and Current Advances in Drug Delivery—A Comprehensive Review of the Literature

Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor in adults with an extremely poor prognosis. There is a dire need to develop effective therapeutics to overcome the intrinsic and acquired resistance of GBM to current therapies. The process of developing novel anti-neoplastic drugs from bench to bedside can incur significant time and cost implications. Drug repurposing may help overcome that obstacle. A wide range of drugs that are already approved for clinical use for the treatment of other d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 172 publications
(274 reference statements)
0
13
0
Order By: Relevance
“…Drug repositioning also called as repurpose drugs is a growing concept that explores pre-existing a well-established drug to treat diseases aside from the intended ones. This concept results in lowering the overall developmental cost, time and risk assessments, as the efficacy and safety of the original drug have already been well accessed and approved by regulatory authorities [138]. In case of GSCs, repurpose drugs are being tested and have shown encouraging results.…”
Section: Drugs Targeting Metabolic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug repositioning also called as repurpose drugs is a growing concept that explores pre-existing a well-established drug to treat diseases aside from the intended ones. This concept results in lowering the overall developmental cost, time and risk assessments, as the efficacy and safety of the original drug have already been well accessed and approved by regulatory authorities [138]. In case of GSCs, repurpose drugs are being tested and have shown encouraging results.…”
Section: Drugs Targeting Metabolic Pathwaysmentioning
confidence: 99%
“…Similarly glimepiride, another anti-diabetes drug, impairs GSCs by targeting glycolytic flux and increases its radio sensitivity to GBM [791]. Further, more repurpose drugs need to be identified that can effectively target GSCs along with its associated mechanism before it can be used in clinical application [138].…”
Section: Drugs Targeting Metabolic Pathwaysmentioning
confidence: 99%
“…In fact, scholars have demonstrated that the BBB in patients with malignant gliomas is frequently damaged to varying degrees. The tolerance of gliomas themselves to anticancer drugs is the most essential cause of chemotherapy failure ( 5 ). Therefore, revealing the mechanisms of resistance is of crucial importance for reducing or eliminating the phenomenon of chemoresistance.…”
Section: Mechanisms Of Chemotherapy Resistance In Gliomasmentioning
confidence: 99%
“…As a result of these developments, a plethora of approved drugs, initially developed for other malignancies or non-oncological indications, are now being (re)evaluated as potential treatments for GBM patients [ 166 , 194 , 220 , 221 , 222 ]. An overview of previous and ongoing clinical trials assessing repurposed drugs in GBM patients is presented in Table 2 .…”
Section: Drug Repurposing For Glioblastomamentioning
confidence: 99%